A qualitative study of digital citizenship practices and the fear of missing out: perceptions of middle school students and principals - Dalinghaus, Lucus Joseph (Kansas State University, 2023)
The purpose of this study was to determine the perceptions of middle school students and principals regarding digital citizenship practices and how these practices and behaviors are impacted by the Fear of Missing Out (FoMO). A phenomenological qualitative research study was conducted through three student focus groups, one principal focus group, and six individual student interviews to answer the research questions. The investigation revolved around four topics: digital citizenship, interconnected digital platform usage, social media, and FoMO. Focus group and interview transcripts were transcribed and coded to generate five themes. The five themes that emerged from the data included: (1) Balancing Connections, Communication, and Appropriate Practices, (2) Relationships, Responsibilities, and Finding an Online Identity of Interests, (3) Characteristics of a Positive Digital Citizen, (4) Emotions and Feelings Shaped by Experiences, and (5) Disconnect Between an Understanding of Digital Citizenship and Reality of Practice. Based upon the results of the study, the researcher recommends it would be appropriate for schools to implement technology classes and programs that educate students on how to properly utilize interconnected digital platforms and devices. Educating students about how to use the devices, the purpose of social media, and how to be a positive digital citizen would be beneficial. The FoMO influences students and should be considered when designing policies and school rules regarding interconnected digital media platforms. Furthermore, based on the results of this research study, efforts to develop positive digital citizenship habits should include direct instruction on interpersonal communication. Future research should center around the psychology behind automatic responses and the realization of conducting tasks without cognizant awareness. Continued dialogue with students to better understand this phenomenon is warranted.
Keywords: FoMO; Digital citizenship; Social media; Smartphones; Cell phones; Mental health